Antiradical activity, antimutagenic and antigenic properties of enzymatic bovine colostrum hydro lysates - Halavach, Tatsiana M.; Tarun, Ekaterina I.; Dudchik, Natalia V.; Romanovich, Roman V.; Bubra, Ilona A.; Kurchenko, Vladimir P. (Experimental Biology and Biotechnology, 2018)
A comparative analysis of protein and peptide profile, biological active properties of hydrolysed bovine colostrum obtained using various endopeptidases (alcalase and neutrase) was performed. It was found that hydrolysis with alcalase and ultrafiltration led to increase in antioxidant activity of the peptide fraction by 7.1 times whereas using neutrase by 3.5 times. Maximum antimutagenic effect was shown for experiment with alcalase, that attained 10.0 –29.6 % for strain Salmonella typhimurium TA 98 and 12.5–32.4 % for strain TA 100. Ultrafiltrate of hydrolysate using alcalase is enriched with specific short-chain peptides which determine its relatively high antimutagenic and antiradical properties. According to SDS-electrophoresis and reaction of immunoprecipitation alcalase effectively cleaves β-lactoglobulin, that provides a hydrolysate producing with low allergen potential. Neutrase cleaves this protein substrate partially. Using immunochemical analysis lactoferrin was detected in all samples of hydrolysed colostrum. In accordance with experimental data the raise in antioxidant and antimutagenic potential and also the decline in antigenic properties of hydrolysed colostrum are due to an increase in depth of proteolysis.